2002
DOI: 10.1103/physrevlett.88.085505
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Photoinduced Ring Opening of Benzene

Abstract: The chemical transformation of crystalline benzene into an amorphous solid (a-C:H) was induced at high pressure by employing laser light of suitable wavelengths. The reaction was forced to occur at 16 GPa, well below the pressure value (23 GPa) where the reaction normally occurs. Different laser sources were used to tune the pumping wavelength into the red wing of the first excited singlet state S(1)((1)B(2u)) absorption edge. Here the benzene ring is distorted, presenting a greater flexibility which makes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
112
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 22 publications
6
112
0
1
Order By: Relevance
“…The pressure shift of the exciton band is shown in Fig. 3 Upper, together with the data relative to the S 0 3 S 1 transition from the OP absorption spectra (21). The discrepancy between the two sets of data is large (Ϸ1 eV at 14 GPa) and is attributed to the method used to estimate the energy gap in the saturated OP absorption spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure shift of the exciton band is shown in Fig. 3 Upper, together with the data relative to the S 0 3 S 1 transition from the OP absorption spectra (21). The discrepancy between the two sets of data is large (Ϸ1 eV at 14 GPa) and is attributed to the method used to estimate the energy gap in the saturated OP absorption spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The threshold pressure for activating the reaction is considerably lowered when the crystal is irradiated by laser light of suitable energy (21), which suggests the active role of excited states in the reaction. One open and intriguing question is how these findings are linked to recent results showing the existence of a critical intermolecular C-C distance used to induce the reaction in crystalline benzene (13), which implies that the microscopic mechanism of pressure-induced reactivity can be modeled only once the role of the excited states is fully understood.…”
mentioning
confidence: 99%
“…It is therefore evident that these reactions become more and more relevant with increasing pressure because the increasing density of the materials results in reduced intermolecular distances that favor the interaction between excited and groundstate molecules. The efficiency of these processes is also attested to by several reactions occurring in pure condensed unsaturated hydrocarbons triggered by 2-photon (TP) excitations realized with cw (continuous wave) low-power laser sources that, because of the small cross-section of TP transitions, ensure catalytic amounts of excited species (5,6,12,15).Among simple molecular systems, water is of primary importance because of its abundance on the Earth's surface and because it is the most abundant polyatomic molecule in the visible universe (16). In addition, chemical reactions taking place in liquid water are essential for many processes in environmental science and biology.…”
mentioning
confidence: 99%
“…Combining the data from X-ray diffraction at room temperature as a function of pressure, and an estimate of the amplitude of thermal motion as a function of temperature, it has been shown that all the points on the stability line correspond to the same instantaneous minimum distance between nearest neighbors along the a axis, which is also the calculated critical distance for the formation of a dimer, as shown in figure 1 which is the seed for the reaction initiation [8]. The most interesting aspect, in view of understanding and exploiting photochemistry, is that irradiation with light at λ ≤ 514 nm induces the same reaction at 16 GPa, very far from the critical structural and dynamical conditions to achieve the reactive approach of two neighbor molecules [9]. TP excitation profiles in the region 550-450 nm were measured up to 12 GPa.…”
Section: Benzene: Reactivity Triggered By Formation Of Dimersmentioning
confidence: 99%
“…When the reaction is performed starting from the pure, thermally annealed monoclic phase II, the reaction threshold [8]. Blue dots indicate the experimental threshold point for spontaneous transformation into amorphous hydrogenated carbon, the green dot indicates the threshold pressure at room temperature at which the same transformation can be induced by photoactivation with light at λ ≤ 514 nm [9]. (b) unit cell of the P2 1 /c crystal structure of benzene (phase II).…”
Section: Benzene: Reactivity Triggered By Formation Of Dimersmentioning
confidence: 99%